Grokking Artificial Intelligence Algorithms, Video Edition - Hurbans, Rishal; Hurbans, Rishal (Manning Publications, 2020)
From start to finish, the best book to help you learn AI algorithms and recall why and how you use them. Linda Ristevski, York Region District School Board Grokking Artificial Intelligence Algorithms is a fully-illustrated and interactive tutorial guide to the different approaches and algorithms that underpin AI. Written in simple language and with lots of visual references and hands-on examples, you'll learn the concepts, terminology, and theory you need to effectively incorporate AI algorithms into your applications. And to make sure you truly grok as you go, you'll use each algorithm in practice with creative coding exercises--including building a maze puzzle game, performing diamond data analysis, and even exploring drone material optimization. about the technology Artificial intelligence touches every part of our lives. It powers our shopping and TV recommendations; it informs our medical diagnoses. Embracing this new world means mastering the core algorithms at the heart of AI. about the book Grokking Artificial Intelligence Algorithms uses illustrations, exercises, and jargon-free explanations to teach fundamental AI concepts. All you need is the algebra you remember from high school math class. Explore coding challenges like detecting bank fraud, creating artistic masterpieces, and setting a self-driving car in motion. what's inside Use cases for different AI algorithms Intelligent search for decision making Biologically inspired algorithms Machine learning and neural networks Reinforcement learning to build a better robot about the audience For software developers with high school-level algebra and calculus skills. about the author Rishal Hurbans is a technologist, founder, and international speaker. This book takes an impossibly broad area of computer science and communicates what working developers need to understand in a clear and thorough way. David Jacobs, Product Advance Local The most comprehensive content I have seen on AI algorithms. Karan Nih, Classic Software Solutions This book removes the fear of stepping into the mechanics of AI. Kyle Peterson, University of Iowa Athletics NARRATED BY JEROMY LLOYD AND JULIE BRIERLEY.